Risk factors for intimate partner emotional violence among women in union in Uganda - Nakitto, Resty; Nzabona, Abel; Wandera, Stephen Ojiambo (Frontiers in Sociology, 2023)
Introduction Despite the growing evidence of the prevalence of gender-based violence in Uganda, less is known about the factors influencing intimate partner emotional violence (IPEV) among married women in the country. This study investigated the social demographic factors associated with IPEV among married women aged 15 years and older. Data and methods The study used the 2016 Uganda Demographic Healthy Survey (UDHS) data. A weighted sample of 5,642 women who had been in a union was selected. A binary logistic regression model was fitted to analyze the predictors of IPEV. Results Almost four in 10 (38%) married women experienced IPEV. Witnessing parental violence (OR = 1.37, CI = 0.59–0.92), partner's controlling behavior (OR = 4.26, CI = 3.29–5.52), and attaining age 35+ (OR = 1.44, CI = 1.06–1.95) increased the odds of IPEV. Residing in rural areas (OR = 0.004, CI = 0.48–0.99) and having higher education (OR = 0.51, CI = 0.26–1.00) decreased the odds of IPEV. Conclusion and implications Witnessing parental violence, alcohol consumption, age, place of residence, partner's controlling behavior, and level of education influence IPEV among married women in Uganda. The findings have several implications including strengthening IPEV-prevention campaigns, women empowerment, and alcohol consumption regulations.